Coaching Co-Teachers: Increasing Specialized Instruction in Inclusive Settings. (November 2021) - Cook, Sara Cothren; Collins, Lauren W.; Madigan, Jennifer; McDuffie Landrum, Kimberly; Cook, Lysandra
Although the co-teaching service delivery model is the most commonly used service delivery model used to support co-teachers in the inclusive setting (Cook et al., 2017), research indicates that co-teachers may need support in order to increase the use of specialized instruction to meet the individual needs of students with disabilities (Scruggs et al., 2007). In this manuscript, we provide a process for instructional coaches to use to (a) develop and deliver effective professional development and (b) coach co-teachers. This process maximizes the potential of the co-teaching service delivery model in improving educational outcomes for students with disabilities.